An avocado a day : more than 70 recipes for enjoying nature's most delicious superfood - Ferroni, Lara (Sasquatch Books, 2017)
"Nutty, buttery, and rich in fiber and healthy fat, avocados are a well-known nutrition booster. Making them part of your daily diet can help improve your health. This cookbook is devoted to avocados and includes simple and delicious recipes for every time of day -- yes, including breakfast and dessert! Avocado lovers will be inspired to go beyond mashing one into guacamole or adding a slice to a sandwich."--Back cover.